2006
DOI: 10.1016/j.bbadis.2005.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chaperone α-crystallin prevents detrimental effects of neuroinflammation

Abstract: Silver nitrate administration stimulates immune activation, inflammation and deterioration in cell function. It is well established that hippocampal and cortical tissue are susceptible to degeneration in responses to insult such as oxidative stress or infection. This study was designed to investigate the prophylactic effect of alpha-crystallin, a major chaperone lens protein comprising of alpha-A and alpha-B subunits in inflammation induced mice. Mice were divided into three groups (n=6 in each), control, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…␣ -Crystallins can reduce the release of inflammation-induced cytokines, and it has been suggested that ␣ -crystallin has the potential to act as an anti-inflammatory agent in the neuroprotective process [9,10] . Protein misfolding and inclusion formation play important roles in neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…␣ -Crystallins can reduce the release of inflammation-induced cytokines, and it has been suggested that ␣ -crystallin has the potential to act as an anti-inflammatory agent in the neuroprotective process [9,10] . Protein misfolding and inclusion formation play important roles in neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a class of heat shock protein, ␣ -crystallin exhibits chap- erone-like properties, including the ability to prevent the precipitation of denatured proteins and to increase cellular tolerance to stress [8] . Masilamoni et al [9,10] found that ␣ -crystallin pretreatment prevented TNF-␣ and NO production in lipopolysaccharide (LPS)-activated astrocytes in an inflammation-induced mouse model. This suggested a protective function by ␣ -crystallin in inflammation-triggered neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings indicate that, in AMD, both MsrA and α-crystallin accumulate in the drusen, and the nature of their physical and molecular interactions under pathological conditions is not known. Further, α-crystallins are neuroprotective in multiple neurodegenerative diseases [71,[88][89][90][91][92] , and given the fact that oxidation of the methionine residues inhibits the chaperone function of crystallins, it is plausible that modulation (by overexpression) of the Msr activity may be beneficial in the treatment of these diseases. In addition, aging contributes to increased oxidation of methionine in proteins so that MsrA alone or in combination therapy could offer significant and long-term protection.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Result from EBV Infection-One of the most debated autoantigens in MS is crystallin alpha-B (CRYAB), a heat shock protein with suppressive effects on (neuro)inflammation through chaperone-like activities (74). CRYAB binds a spectrum of unfolded or aggregated proteins, and it is highly expressed as a 24-subunit multimer in the eye lens, where it is a target antigen in patients with intraocular inflammation (75).…”
Section: Cryab: Igg Binding the N-terminal Region Maymentioning
confidence: 99%